Two dimensional cellular automata simulation of graingrowth during solidification and recrystallization; IOP Conference Series: Materials Science and Engineering; Vol. 71: International Scientific Conference of Young Scientists: Advanced Materials in Construction and Engineering - Zinovjeva O. S.; Zinovjev A. V.; Ploshikhin V.; Romanova V. A. Varvara Aleksandrovna; Balokhonov R. R. Ruslan Revovich (2015, 2015)
Title screen